MiR-27b inhibits gastric cancer metastasis by targeting NR2F2. Issue 2 (14th November 2016) - Feng, Qingzhao; Wu, Xionglin; Li, Fuchao; Ning, Beibei; Lu, Xiaofeng; Zhang, Yin; Pan, Ying; Guan, Wenxian
Abstract: Increasing attention is focused on the down-regulation of miRNAs in cancer process. Nuclear receptor subfamily 2 (NR2F2, also known as COUP-TFII) is involved in the development of many types of cancers, but its role in gastric cancer remains elusive. In this experiment, oncomine and Kaplan-meier database revealed that NR2F2 was up-regulated in gastric cancer and that the high NR2F2 expression contributed to poor survival. MicroRNA-27b was targeted and down-regulated by NR2F2 in human gastric cancer tissues and cells. The ectopic expression of miR-27b inhibited gastric cancer cell proliferation and tumor growth in vitro and in vivo . Assays suggested that the overexpression of miR-27b could promote MGC-803 cells' migration and invasion and retard their metastasis to the liver. In addition, down-regulation of miR-27b enhanced GES-1 cells' proliferation and metastasis in vitro . These findings reveal that miR-27b is a tumor suppressor in gastric cancer and a biomarker for improving patients' survival.